SYNTACTICAL REALIZATION OF MODAL SIGNIFICANCE OF UNCERTAINTY - Solomchak, N. F. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article the types of freely divided and semi-fraseologised syntactical constructions which express modal significance of uncertainty are analysed, their functional parameters are clarified.